1999
DOI: 10.1097/00006534-199911000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Areolar Reconstruction Using a Neurocutaneous Island Flap Based on the Medial Antebrachial Cutaneous Nerve

Abstract: Sensory reconstruction has recently been stressed in breast reconstruction. However, there are no reports concerning the reconstruction of a sensitive areola. The bilateral reconstruction of a sensitive areola using a neurocutaneous flap based on the medial antebrachial cutaneous nerve is reported. The flap was harvested from the distal third of the forearm as an island flap and tunneled to reach the apex of the new breast, which was previously reconstructed using a 135-cc, gel-filled, silicone prosthesis cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Although this does again present an opportunity for improvement, even nipple-sparing mastectomies often have reduced sensation, and attempts at innervated flaps have mostly been underwhelming. 20 However, despite the expected decline in breast sensation, a majority (>50.0%) of women felt that their sexual confidence was improved with nipple aerolar complex (NAC) reconstruction. This has been validated in other reports showing that NAC reconstruction often results in improved overall aesthetic and patient satisfaction when all other factors are the same.…”
Section: Discussionmentioning
confidence: 99%
“…Although this does again present an opportunity for improvement, even nipple-sparing mastectomies often have reduced sensation, and attempts at innervated flaps have mostly been underwhelming. 20 However, despite the expected decline in breast sensation, a majority (>50.0%) of women felt that their sexual confidence was improved with nipple aerolar complex (NAC) reconstruction. This has been validated in other reports showing that NAC reconstruction often results in improved overall aesthetic and patient satisfaction when all other factors are the same.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of the cutaneous arterial system showed that sensitive nerves of the skin were consistently accompanied by arteries and veins with an axial course that often provided the dominant vascular supply to the skin region (Taylor, Gianoutsos, & Morris, ). Since then, several neurocutaneous flaps have been described, mainly in the extremities (Bertelli & Pagliei, ; Bertelli, Pereira Filho, & Ely, ; Oberlin, Azoulay, & Bhatia, ; Yildirim, Akan, Gideroglu, & Akoz, ).One of the most popular of them is the distally based sural flap, employed as a routine technique for foot and ankle reconstruction (Xu & Lai‐Jin, ).Many modifications have been done to this flap to improve the reliability of the skin island (Liu et al, ; Tan, Atik, & Bekerecioglu, ).In 1992, Masquelet et al () introduced the superficial peroneal neurocutaneous flap, a redefinition of the previously described lateral supramalleolar flap, to underline the key role of the feeding vessels of the superficial peroneal nerve in the survival of skin paddle.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Wang, Chai, Wen, Han, and Cheng () described a modification of this flap, employing as a pedicle an anterior tibial artery perforator. Also, in the upper limb these flaps have been anatomically studied and clinically employed, for defects of the forearm, hand and fingers (Bertelli et al, ; Bertelli & Pagliei, ; Chen, Tang, & Zhang, ).Several advantages are offered by neurocutaneous flaps, particularly in the distal third of the leg and foot, including no need to sacrifice source vessels, easy and fast dissection with reduced operative time, if compared to free flaps (Fourn, Caye, & Pannier, ). Despite these advantages, many surgeons do not employ neurocutaneous flaps because of controversial anatomy and a certain unpredictability of the extension of the skin island that can be safely harvested (Akyürek, Safak, Sönmez, Ozkan, & Keçik, ).…”
Section: Introductionmentioning
confidence: 99%